Identifying Yalom’s group therapeutic factors in anonymous mental health discussions on Reddit: a mixed-methods analysis using large language models, topic modeling and human supervision - Ferizaj, Drin; Lalk, Christopher; Lahmann, Nils; Strube-Lahmann, Sandra; Rubel, Julian (Frontiers in Psychiatry, 2025)
IntroductionOnline communities provide valuable, peer-led spaces for discussing mental health issues, offering support that can complement traditional therapy. In this study, we adopt an interpretive approach by applying Yalom's group therapeutic factors to explore how mental health–focused Reddit discussions may reflect group therapy processes.MethodsWe propose a practical methodological framework for large-scale qualitative research. Using a mixed-methods approach, we integrate advanced Natural Language Processing (NLP) techniques—including Large Language Models (GPT-3.5 Turbo 16k), cosine similarity, and BERTopic—with human validation to analyze 6,745 comments from mental health–focused Subreddits.ResultsThe results show that a large portion of the data can be interpreted through Yalom's therapeutic factors, such as Instillation of Hope, Group Cohesion, and Altruism, suggesting a generally supportive and empathetic online environment. However, unfiltered negative dynamics, including shared suffering and maladaptive coping strategies, also appeared in the discussions.DiscussionBy grounding NLP-based analyses in a well-established therapeutic framework and incorporating human expertise, we demonstrate a transparent, scalable approach to examining large-scale online mental health data. These findings underscore the potential of online communities for enhancing peer-led mental health support, while emphasizing the importance of theoretical grounding in interpreting such digital spaces.